ANALISIS KEBIJAKAN PUBLIK MENUJU TATA PEMERINTAHAN YANG BERSIH DAN BERWIBAWA - Wiwin Winangsih (FISIP Universitas Langlangbuana, 2019)
One of the national development agenda is to create clean and authoritative governance. It required policy measures directed at institutional change and systems management; quality of human resources, and system of effective supervision and inspection. Policy analysis, in a broad sense, involving the results and knowledge in the policy process. Policy analysis is expected to generate and transform information about the values​​, facts, and actions. The purpose of this paper to analyze the extent to which public policy analysis towards clean and authoritative governance. The method of writing done with a review of relevant literature on the theme of public policy analysis towards clean and authoritative governance. The results of this study indicate that to realize the clean and authoritative Governance, the organization of state policy should be directed to: (1) Complete the prevention of abuse of power in the form of corruption practices; (2) Improve the quality of the organization of the state administration; and (3) Increasing the empowerment of the community in the implementation of development.